The Factors of Cronic Kidney Disease (CKD) on Public Transportation Drivers in Jember Regency - Novita Firdaus; Hadi Prayitno; Isa Ma'rufi (Humanistic Network for Science and Technology (HNST), 2020)
Chronic kidney disease (CKD) is a condition where the kidneys cannot filter waste properly as indicated by the estimated Glomerular Filtration Rate (eGFR)